Demographic response to patch destruction in a spatially structured amphibian population. Issue 5 (3rd July 2018) - Cayuela, Hugo; Besnard, Aurélien; Quay, Ludivine; Helder, Rémi; Léna, Jean‐Paul; Joly, Pierre; Pichenot, Julian
Abstract: Economic activities such as logging and mineral extraction can result in the creation of new anthropogenic habitats that host specific biodiversity, including protected species. However, the legislation in many Western European countries requires the rehabilitation of "damaged" areas following logging and mining operations, which can eliminate these early successional habitats. Conservation managers face a dilemma in these situations, but often lack knowledge about the impacts of environmental rehabilitation on the population dynamics of pioneer species and so are unable to take this into account in their actions. We investigated the demography of a spatially structured population of an endangered amphibian ( Bombina variegata ) that uses waterbodies created by logging activities as breeding sites. Using capture–recapture (CR) data collected during a 9‐year study period, we examined how the destruction of breeding patches due to environmental rehabilitation affected adult survival and the long‐term population growth rate. For this purpose, we used recently developed capture–recapture multievent models to estimate survival and dispersal rates in the spatially structured population. We then used these estimates to simulate population trajectories and viability depending on differing frequency of breeding patch destruction. The multievent models revealed that dispersal not resulting from patch loss was relatively high and was sex biased. They also highlighted that patch destruction had a negative impact on adult survival. Moreover, simulations showed that the increase in patch destruction frequency had a strong negative influence on the population growth rate, even when the number of patches remained constant over time. This impact was intensified if female fecundity was also affected. Synthesis and applications . Our study quantifies for the first time the detrimental effect of habitat rehabilitation on the population dynamics of an endangered, pioneer species. Our results show that this deleterious impact of patch destruction could be reduced by certain management practices, such as avoiding the systematic rehabilitation of the breeding patches and compensating for patch destruction by creating substitute breeding patches. Abstract : Our study quantifies for the first time the detrimental effect of habitat rehabilitation on the population dynamics of an endangered, pioneer species. Our results show that this deleterious impact of patch destruction could be reduced by certain management practices, such as avoiding the systematic rehabilitation of the breeding patches and compensating for patch destruction by creating substitute breeding patches.